Effects of microfinance bank credit on small and medium scale businesses: Evidence from Alimosho LGA, Lagos State - Charles Onyeiwu; Obumneke Bob Muoneke; Adekunle M. Abayomi (The Journal of Entrepreneurial Finance (JEF), 2020)
The purpose of this research is to examine the impact of microfinance bank credit and its debt servicing on the profitability of SMEs in Alimosho Local Government Area, Lagos State, Nigeria. A survey was carried out involving 387 SMEs in Alimosho LGA, Lagos State and information was extracted using a well-structured questionnaire to answer research hypotheses raised. Evidence from the simple linear regression outputs of SPSS v.25 shows that that MFBs loans and MFBs loans debt service deteriorates significantly the profitability of selected SMEs in the Alimosho local government area of Lagos state. Policy recommendations to the Federal Government, commercial banks, microfinance banks and the apex bank are; Micro Finance Banks (MFBs) should lighten the terms of lending including increasing the duration of the loans to ease repayment by SMEs; MFBs should adopt flexible requirements suitable for small-scale and medium enterprises as pertaining documentation and other specialized services to engender SMEs growth; MFBs should cover the lacuna of ex-post verification by setting up a digital platform where progress of projects cum businesses for which loans are granted are effectively monitored at lesser costs.
Keywords: G21; G32; M13; R51; 650; Microfinance Bank Credit; SMEs; Profitability; Debt servicing; Lagos